Karakteritik sifat alir bubuk teh hijau yang diproses dengan metode penepung berbeda - Mukhammad Iqbal Prawira-Atmaja; Sugeng Haryanto; Hilman Maulana; Shabri Shabri; Dr. Dadan Rohdiana (Jurnal Penelitian Teh dan Kina, 2018)
Recently, the public interest in green tea powder is increasing. Green tea powder is produced through the process stage: withering in hot steam, drying, and reducing size. The size reduction process on green tea powder is an important step because it will affect the characteristics of the powder flow properties. This study aims to determine the flow properties of green tea powder processed by different milling method. The milling method used are disc milling (DM) and stone milling (SM). Green tea powder was analyzed including moisture content, particle size distribution using dynamic laser scattering method, determined of bulk density (ρb), and tapped density (ρtap) to find out the Carr Index (CI) and Hausner Ratio (Hr). In addition, the lightness of color and shape and morphology of green tea powder were observed with SEM. The results showed that green tea powder produced from different milling methods have a Carr Index of 15 with “Good” flow properties. DM method produced darker green tea powder with L value (lightness) 49.91 and larger particle size (D50: 38.6 µm) compared with green tea powder produced by the SM method. Determination of flow properties of green tea powder can be applied for the utilization and development of food products and pharmaceutical products based on green tea powder.